2017
DOI: 10.1111/joim.12715
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ventricular‐arterial coupling during a 2‐year physical activity programme in patients with rheumatoid arthritis: a prospective substudy of the physical activity in rheumatoid arthritis 2010 trial

Abstract: Abstract. Sarajlic P, Frid en C, Lund LH, Manouras A, Venkateshvaran A, Larsson SC, Nordgren B, Opava CH, Lundberg IE, B€ ack M

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
2
25
1
Order By: Relevance
“…A specific effect on calcification as opposed to other vascular changes is further supported by the lack of association of chemerin with Aix which in addition to calcification also depends on other structural changes of the vasculature, such as fibrosis and endothelial dysfunction as well as diastolic heart function . However, our finding that chemerin did not associate with arterial stiffness is in contrast to studies in nonrenal patients , suggesting a differential association between chemerin not only between CAC and Aix but possibly also between renal and nonrenal patients.…”
Section: Discussionsupporting
confidence: 58%
“…A specific effect on calcification as opposed to other vascular changes is further supported by the lack of association of chemerin with Aix which in addition to calcification also depends on other structural changes of the vasculature, such as fibrosis and endothelial dysfunction as well as diastolic heart function . However, our finding that chemerin did not associate with arterial stiffness is in contrast to studies in nonrenal patients , suggesting a differential association between chemerin not only between CAC and Aix but possibly also between renal and nonrenal patients.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, anti‐tumour necrosis factor‐α therapy resulted in reduced PWV after a 3‐month follow‐up period in patients with inflammatory arthropathy . Additionally, the Physical Activity in RA (PARA) trial has shown that moderate intensity physical activity resulted in increased E/A and a trend towards decreased PWV and augmentation index, suggesting the reversal of ventricular–arterial decoupling. Finally, in psoriatic patients, novel biological agents reduced arterial stiffness, central aortic pressure and wave reflections, and improved LV longitudinal deformation and LV twisting‐untwisting within 4 months, through inflammatory and oxidative stress burden reduction …”
Section: Ventricular–arterial Coupling In Systemic Inflammatory Diseasementioning
confidence: 99%
“…A two-year program of Physical Activity in RA (PARA) 2010 was designed to investigate its feasibility and to study changes in self-reported variables, physical capacity measurements, in ammation, pain modulation and cardiovascular risk 11 . Positive changes during the two-year study period were observed for HEPA participants concerning symptoms and physical capacity [12][13] and cardiovascular risk factors [14][15] , while pain modulation did not change 16 . In this context we performed a pilot study with focus on protein adaptations in muscle tissue in a subgroup of people with RA who consented to repeated muscle biopsies.…”
Section: Introductionmentioning
confidence: 90%